The Anti-Oxidant and Antitumor Properties of Plant Polysaccharides - Jiao, Rui; Liu, Yingxia; Gao, Hao; Xiao, Jia; So, Kwok Fai (The American journal of Chinese medicine (1979), 2016)
Oxidative stress has been increasingly recognized as a major contributing factor in a variety of human diseases, from inflammation to cancer. Although certain parts of signaling pathways are still under investigation, detailed molecular mechanisms for the induction of diseases have been elucidated, especially the link between excessive oxygen reactive species (ROS) damage and tumorigenesis. Emerging evidence suggests anti-oxidant therapy can play a key role in treating those diseases. Among potential drug resources, plant polysaccharides are natural anti-oxidant constituents important for human health because of their long history in ethnopharmacology, wide availability and few side effects upon consumption. Plant polysaccharides have been shown to possess anti-oxidant, anti-inflammation, cell viability promotion, immune-regulation and antitumor functions in a number of disease models, both in laboratory studies and in the clinic. In this paper, we reviewed the research progress of signaling pathways involved in the initiation and progression of oxidative stress- and cancer-related diseases in humans. The natural sources, structural properties and biological actions of several common plant polysaccharides, including Lycium barbarum, Ginseng, Zizyphus Jujuba, Astragalus lentiginosus, and Ginkgo biloba are discussed in detail, with emphasis on their signaling pathways. All of the mentioned common plant polysaccharides have great potential to treat oxidative stress and cancinogenic disorders in cell models, animal disease models and clinical cases. ROS-centered pathways (e.g. mitochondrial autophagy, MAPK and JNK) and transcription factor-related pathways (e.g. NF-[Formula: see text]B and HIF) are frequently utilized by these polysaccharides with or without the further involvement of inflammatory and death receptor pathways. Some of the polysaccharides may also influence tumorigenic pathways, such as Wnt and p53 to play their anti-tumor roles. In addition, current problems and future directions for the application of those plant polysaccharides are also listed and discussed.